Teacher development in higher education : existing programs, program impact, and future trends - Simon, Eszter; Pleschová, Gabriela (New York : Routledge, 2013)
"Concerns about the quality of teaching and learning in higher education have given rise to teacher development programs and centers around the world. This book investigates the challenges and complexities of creating instructional development programs for present and future academics. Using case studies from a variety of countries, including Estonia, Singapore, the United States, and the United Kingdom, it examines issues that are important for higher education researchers as well as for higher education managers. The book introduces different responses from around the world to the need to improve teaching in higher education, demonstrates many different ways success may be understood, and investigates what factors may influence the results of instructional development. Contributors use these factors, as well as those found in the related literature, to explain program success through theoretical frameworks. This book also provides input for higher-education managers by pointing out how the local context and both institutional and national policy-making may help or hinder the effective preparation of professors for their teaching responsibilities"--
pt. I. Training for what? : instructional development for graduate students -- pt. II. Using programme assessments to improve programme design -- pt. III. Top-down determinants of success in instructional development programmes -- pt. IV. Theorizing about instructional development.
Includes bibliographical references and index.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: College teachers -- Training of -- Cross-cultural studies; Electronic books